2016
DOI: 10.1159/000443988
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 Concentrations Reflect Sex Differences in Mineral Metabolism and Growth in Early Infancy

Abstract: Background: The role of fibroblast growth factor 23 (FGF23) in the regulation of mineral homeostasis in early life is inadequately understood. We aimed to explore the effects of vitamin D supplementation on serum FGF23 and to elucidate longitudinal changes in FGF23, in addition to studying its association with mineral metabolism in early infancy. Methods: Altogether 113 healthy infants received vitamin D3 10, 30 or 40 µg/day from age 0.5 to 3.0 months. Cord blood at birth and capillary blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
(64 reference statements)
2
6
0
Order By: Relevance
“…The cohort presented in our study included older and more male participants compared with participants in this study, where female CKD participants were observed to have higher iFGF-23 levels compared with CKD males, providing a potential explanation for the disparity. This gender difference in FGF-23 levels is consistent with reports in both the very young [41] and adults [42, 43]. One postulation is that estradiol is a phosphaturic agent [44] and the loss of this hormone with onset of menopause may result in higher sPi levels, contributing to a compensatory increase in FGF-23.…”
Section: Discussionsupporting
confidence: 88%
“…The cohort presented in our study included older and more male participants compared with participants in this study, where female CKD participants were observed to have higher iFGF-23 levels compared with CKD males, providing a potential explanation for the disparity. This gender difference in FGF-23 levels is consistent with reports in both the very young [41] and adults [42, 43]. One postulation is that estradiol is a phosphaturic agent [44] and the loss of this hormone with onset of menopause may result in higher sPi levels, contributing to a compensatory increase in FGF-23.…”
Section: Discussionsupporting
confidence: 88%
“…In small children, the regulatory mechanisms may be different, and there may be regulating factors no longer seen in adulthood. For example, among healthy 3-month old infants, we previously observed that girls presented with almost 50% higher intact FGF23 concentrations than boys (5). This was a novel finding, which is confirmed also in the current large cohort, where the difference between boys and girls at age 1 year was less marked, 8%, but still similar in direction.…”
Section: Discussionsupporting
confidence: 87%
“…Apart from regulation by phosphate, parathyroid hormone (PTH) and 1,25-dihydroxyvitamin D (1,25(OH) 2 D), also other factors are involved (4). We previously demonstrated that intact FGF23 concentrations in early infancy (at age 3 months) differ between sexes, girls having significantly higher concentrations than boys (5).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, two studies have found gender related differences in FGF-23 in infants [63,64]. Considering the newest finding on the role of FGF-23 in vitamin D regulation [14], the gender differences found might be partly due to this connection.…”
Section: Discussionmentioning
confidence: 88%